2007
DOI: 10.1152/ajprenal.00117.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Na+/H+exchanger NHE8 in cultured renal epithelial cells

Abstract: NHE8 is expressed in the apical membrane of the proximal tubule and is predicted to be a Na+/H+ exchanger on the basis of its primary amino acid sequence. Functional characterization of native NHE8 in mammalian cells has not been possible to date. We screened a number of polarized renal cell lines for the plasma membrane Na+/H+ exchangers (NHE1, 2, 3, 4, and 8) and found only NHE1 and NHE8 transcripts in NRK cells by RT-PCR. NHE8 protein is expressed in the apical membrane of NRK cells as demonstrated by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 24 publications
4
56
0
Order By: Relevance
“…It has been documented for several "intracellular" NHE that they can also reside and function on the plasma membrane under certain circumstances, [31][32][33] and dual mitochondrial and plasmalemmal localization has also been reported for the voltage-dependent anion channel VDAC. 34 For the intracellular NHE isoform NHE6, the scaffolding protein RACK1 was recently shown to regulate the balance between plasmalemmal and intracellular localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented for several "intracellular" NHE that they can also reside and function on the plasma membrane under certain circumstances, [31][32][33] and dual mitochondrial and plasmalemmal localization has also been reported for the voltage-dependent anion channel VDAC. 34 For the intracellular NHE isoform NHE6, the scaffolding protein RACK1 was recently shown to regulate the balance between plasmalemmal and intracellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal anti-NHE1 antibody (clone 4E9) was obtained from Calbiochem (Temecula, CA); monoclonal anti-NHE8 antibody has been described before. 32 …”
Section: Immunoprecipitation Cell-surface Biotinylation and Immunobmentioning
confidence: 99%
“…NRK cells endogenously express NHE8 at the plasma 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 membrane. Using the latter cells, Moe et al demonstrated that NHE8 is sensitive to amiloride [190].…”
Section: Slc9a8 -Nhe8mentioning
confidence: 99%
“…Goyal et al (2003Goyal et al ( , 2005 described a new member of the family of mammalian NHE exchangers, the NHE8 isoform. This new isoform mediates Na + -dependent acid extrusion across the apical membrane of proximal tubule cells (Zhang et al 2007). NHE8-mediated transport is retained in NHE3/NHE2 null mice and can be inhibited by EIPA (Choi et al 2000;Zhang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…NHE8 is a recently identified renal Na + /H + antiporter isoform (Goyal et al 2003) that has been localised to the apical membrane of the rat proximal tubule (Goyal et al 2005) and is highly EIPA sensitive (Zhang et al 2007). Interestingly, expression of the NHE8 isoform diminishes with age (Becker et al 2007).…”
Section: Introductionmentioning
confidence: 99%